The contribution of social support to children and adolescents' self-perception: The mediating role of bullying victimization. (April 2016) - Mishna, Faye; Khoury-Kassabri, Mona; Schwan, Kaitlin; Wiener, Judith; Craig, Wendy; Beran, Tanya; Pepler, Debra; Daciuk, Joanne
Abstract: The purpose of this article is to report on a study that explores the linkages among self-perception, perceptions of social support, and bullying involvement among children and youth, with a focus on how bullying victimization mediates the association of social support and self-perception. We employ Harter's multidimensional model of self-esteem (1999; 2012), which highlights the inextricable link of social support to global self-esteem but does not explore the contribution of bullying involvement to this association. Our findings indicate that social support is associated with self-perception, and that traditional victimization mediates the association between social support and self-perception for three self-perception measures: social acceptance, physical appearance, and global self-worth. Contrary to our expectations, cyberbullying victimization was not found to mediate the relationship between social support and self-perception. These findings underscore the importance of exploring both traditional bullying victimization and cyberbullying victimization in relation to social support in order to understand their effect on development and wellbeing. More broadly, this study's finding that social support was a significant buffer to bullying victimization emphasizes the necessity of developing prevention and intervention strategies which are relationship-based and implemented early in young people's lives. Highlights: Adolescents with social support systems are less victimized and have higher levels of self-perception. Traditional bullying victimization and cyberbullying victimization differ in their linkages with self-perception Traditional bullying victimization is strongly associated with self-perception, whereas cyberbullying victimization is not. Traditional bullying victimization mediates the association between social support and self-perception. Interventions that bolster social support may buffer exposure to bullying victimization